Shifts in the Fecal Microbial Community of Cystoisospora suis Infected Piglets in Response to Toltrazuril - Shrestha, Aruna; Metzler-Zebeli, Barbara U.; Karembe, Hamadi; Sperling, Daniel; Koger, Simone; Joachim, Anja (Frontiers in Microbiology, 2020)
The protozoan parasite Cystoisospora suis causes diarrhea and reduced weight gain in suckling piglets. Infections occur in the first days of life; it is transient but can lead to dysbiosis, exacerbating disease and increasing mortality. Cystoisosporosis is effectively controlled by toltrazuril treatment; however, alterations of the gut microbial composition upon infection and treatment have not been investigated. This study evaluated the development of fecal microbiota of C. suis infected piglets in response to treatment with toltrazuril. Thirty-eight conventional piglets were infected with C. suis on the first day of life (dol 1). Twenty-six of them received either parenteral or oral toltrazuril two days later. Fecal samples were collected pre- and post-weaning (dol 1-15 and 31-38) for microbiota analysis using 16S rRNA amplicon sequencing and during dol 5-18 to determine fecal consistency and parasite excretion. All control animals shed parasites at least once and the majority developed diarrhea, while toltrazuril-treated piglets did not excrete parasites and only had low levels of diarrhea. Age-related shifts in the fecal microbiota composition and increase in diversity and species richness were seen until after weaning. Parasite infection disrupted bacterial maturation two weeks after infection. Irrespective of the route of administration, fecal communities of piglets in the treated groups clustered separately and were more diverse compared to that of control piglets during the acute phase of infection on dol 11. Control piglet feces showed higher levels of Fusobacteriaceae and Veillonellaceae, while Ruminococcaceae, Lachnospiraceae, S24-7, Clostridiaceae and Erysipelotrichaceae were more abundant in feces of treated piglets on dol 11. Thereafter, treatment-related effects on the microbial communities were small and mainly detectable on dol 34 (5 days postweaning), potentially indicating that the oral toltrazuril treatment might have had long-term effects on host physiological responses postweaning. Irrespective of the administration route, toltrazuril prevented C. suis-related dysbiosis and maintained species richness and diversity on dol 11. In addition to cystoisosporosis prevention, toltrazuril seems to contribute to the stabilization of the gut microbial development during the suckling phase and thus may reduce the need for antibiotics to control infections with secondary bacterial enteropathogens in C. suis-infected suckling piglets.